High elastic modulus GFRP rebar: A guide to manufacture and design of the influencing parameters - Omar Alajarmeh; Allan Manalo; Dmitry Yatsenko (Composites Part C: Open Access)
Glass fibre reinforced polymer (GFRP) bars are increasingly used as internal reinforcement to concrete infrastructures exposed to harsh environment. A wide range of GFRP bars are commercially available but with high discrepancy in properties due to the inconsistent selection of the manufacturing and design parameters. In contrast to steel bars, producing structural GFRP bars requires a bigger actual than nominal bar diameter claiming higher modulus of elasticity. For the first time, this study reviews the current practice of designing the GFRP bar diameter and reasons behind the discrepancy (lower-upper bound of allowable diameter). It also describes the critical manufacturing parameters through pultrusion process. Moreover, it provides a practical demonstration on systematic design and manufacturing procedures of new GFRP bars both theoretically and experimentally. The guidance provided in this study will be valuable to GFRP manufacturers in consistently producing high modulus GFRP bars (Grade III) without varying much from the nominal diameter.